Psychometric Properties of the Malay Language Version of Knee Injury and Osteoarthritis Outcome Score (KOOS) Questionnaire among Knee Osteoarthritis Patients: A Confirmatory Factor Analysis - Zulkifli, MM; Kadir, AA; Elias, A; Bea, KC; Sadagatullah, AN (Malaysian Orthopedic Association, 2017)
Introduction: This study aimed to cross-culturally adapt a Malay version of Knee Injury and Osteoarthritis Outcome Score (KOOS) and to evaluate its psychometric properties in patients with knee osteoarthritis (OA). Materials and Methods: The English version KOOS was translated into a Malay version using forward and backward translation process, followed by face validity and content validity. Two hundred and twenty-six knee OA patients attending the Outpatient and Orthopaedic Clinics, Universiti Sains Malaysia Hospital, completed the Malay version KOOS. Construct validity using confirmatory factor analysis and internal reliability assessment were performed. Results: The results showed that the original five-factor model with 42 items failed to achieve acceptable values of the goodness of fit indices, indicating poor model fit. A new five-factor model of 26 items demonstrated acceptable level of goodness of fit (comparative fit index= 0.929, incremental fit index= 0.930, Tucker Lewis fit index= 0.920, root mean square error of approximation= 0.073 and Chisquared/ degree of freedom= 2.183) indices to signify a model fit. The Cronbach’s alpha value for the new model ranged from 0.776 to 0.946. The composite reliability values of each construct ranged between 0.819 and 0.921, indicating satisfactory to high level of convergent validity. Conclusion: The five-factor model with 26 items in the Malay version of KOOS questionnaire demonstrated a good degree of goodness of fit and was found to be valid, reliable and simple as an assessment tool for symptoms, pain, activity of daily living, sports and recreational activity and quality of life for Malaysian adults suffering from knee osteoarthritis.